Microlearning y su aporte en el aprendizaje de los estudiantes en el bachillerato técnico en informática de la Unidad Educativa Babahoyo, Periodo Académico octubre 2024- marzo 2025. - Chavez Vargas, Enmy Dayanna (2025)
Currently, learning has been promoted or achieved with the help of technology and the integration of modern educational methodologies. One of them is microlearning, which is a strategy focused on teaching content or short, specific lessons that help facilitate the acquisition of knowledge. This method today has become an essential tool for the training of students, even more so for those who study careers where they must learn a lot of theory. The objective of the project is to evaluate the contribution of microlearning to student learning. The methodology used is composed of a non-experimental design, with a mixed approach, because qualitative and quantitative data collection instruments are applied; while the types of research were descriptive, field and documentary. The units of analysis were determined through probabilistic sampling, who provide relevant data on the importance of microlearning in learning. The results of the research determine that the study subjects conceive microlearning as a transcendental strategy for the educational process; Furthermore, through statistical correlation analysis with the Pearson coefficient, it was established that there is a strong statistical association between the study variables.